2014
DOI: 10.1523/jneurosci.4086-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Transduction without Tip Links in Cochlear Hair Cells Is Mediated by Ion Channels with Permeation Properties Distinct from Those of the Mechano-Electrical Transducer Channel

Abstract: Tip links between adjacent stereocilia are believed to gate mechano-electrical transducer (MET) channels and mediate the electrical responses of sensory hair cells. We found that mouse auditory hair cells that lack tip links due to genetic mutations or exposure to the Ca 2ϩ chelator BAPTA can, however, still respond to mechanical stimuli. These MET currents have unusual properties and are predominantly of the opposite polarity relative to those measured when tip links are present. There are other striking diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(94 citation statements)
references
References 39 publications
5
87
2
Order By: Relevance
“…Based on their properties (single-channel conductance, block by FM1-43 and Ca 2+ selectivity), the unconventional MT currents recorded during development in wild-type mice and those seen under abnormal conditions (in mutants or after tip-link destruction) are manifestations of the same ion channel. Reversepolarity MT currents were previously found to occur embryonically (12), but no subsequent pattern of development or relationship to the normal MT current was evident in that work, and it was further claimed that the reverse-polarity current persisted until at least P10, which we never saw. One hypothesis is that the unconventional channels are associated with the small microvilli that carpet the top surface of hair cells behind the hair bundle, and their transient neonatal appearances are linked.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Based on their properties (single-channel conductance, block by FM1-43 and Ca 2+ selectivity), the unconventional MT currents recorded during development in wild-type mice and those seen under abnormal conditions (in mutants or after tip-link destruction) are manifestations of the same ion channel. Reversepolarity MT currents were previously found to occur embryonically (12), but no subsequent pattern of development or relationship to the normal MT current was evident in that work, and it was further claimed that the reverse-polarity current persisted until at least P10, which we never saw. One hypothesis is that the unconventional channels are associated with the small microvilli that carpet the top surface of hair cells behind the hair bundle, and their transient neonatal appearances are linked.…”
Section: Discussioncontrasting
confidence: 59%
“…A difficulty with assigning significance to the reverse-polarity MT currents stems from them being recorded only under abnormal circumstances, whether by tip-link disruption or mutations that adversely affect mechanotransduction. Previous work had, however, suggested that this type of current may also be present constitutively during hair-cell development (10,12,14,18). More detailed investigation showed that hair cells first displayed mechanical sensitivity around birth, when it was manifested as a reverse-polarity current, always preceding the normal-polarity current ( Fig.…”
Section: Significancementioning
confidence: 89%
See 1 more Smart Citation
“…Reverse-polarity currents also have been reported for TMC1/TMC2 double mutants (14) and other MT-disrupted hair cells (15), keeping open the nomination process for MT channel proteins. Knockout of LHFPL5 produced smaller single MT channel currents and flattened the tonotopic gradient in unitary conductance (for normal polarity motion, reverse-polarity currents appear similar in low-and high-frequency hair cells, although this was not quantified).…”
Section: Reverse-polarity Mechanotransductionmentioning
confidence: 61%
“…The appearance of reversetransduction as a sign that functional bundle remodeling is under way is a tempting avenue to explore. Breaking the tip-link in the transduction complex clearly leads to reverse-transduction within about 5 min in immature hair cells (1,7,12), but it is not known whether the same occurs in adult hair cells. Beurg et al (1) suggest that it does not, at least to any significant extent.…”
mentioning
confidence: 99%